Synthesis and characterization of Pd-on-Pt and Au-on-Pt bimetallic nanosheaths on multiwalled carbon nanotubes - Wang, S.; Jiang, San Ping; Wang, X. (Springer, 2011)
The authors have successfully synthesized Pd-on-Pt (thickness: 12 nm) and Au-on-Pt bimetallic nanosheaths on multiwalled carbon nanotubes (MWCNTs) via a seed-mediated growth approach. Pt nanoparticles as seeds were pre-deposited on MWCNTs with uniform distribution followed by the successive seed-mediated growth of metal atoms reduced by a weak reducing agent, ascorbic acid. The essential role of pre-deposited nanoseed particles on MWCNTs was demonstrated. The as-prepared materials were characterization by transition electron microscopy, energy-dispersive X-ray spectroscopy, and element mapping tools. The current strategy extends the classical seed-mediated growth method to prepare bimetallic nanosheath on MWCNT support.